LAW ENFORCEMENT AGAINST PERFORMERS OF THE CRIME OF MONEY LAUNDERING RESULTING FROM CRIMINAL ACTS OF FRAUD OR EMBEZZER - Suhartono, Nur; Mardani; Sharon, Grace (JILPR Journal Indonesia Law and Policy Review, 2024)
The crime of money laundering is a crime that has a distinctive characteristic, namely, this crime is not a single crime but multiple crimes. This crime is characterized by the form of money laundering, which is a crime that is a follow-up crime or continuing crime, while the main crime or original crime is called a predicate offense or core crime or there are countries that formulate it as an unlawful activity, namely an original crime that produces money and then carries out the laundering process. The crime of money laundering can be seen in Article 1 of Law Number 8 of 2010 which explains that money laundering is any act that fulfills the elements of a criminal act in accordance with the provisions of this law. The problem taken is regarding the proof of the crime of money laundering which is related to the predicate crime. As well as law enforcement against perpetrators of money laundering crimes resulting from criminal acts of fraud or embezzlement. The research method that the author uses is normative juridical research. The conclusion obtained is that the evidence in Law Number 8 of 2010 is one of the anti-money laundering crime efforts which is specifically at the stage of evidence at trial, with efforts to accommodate difficulties at the stage of proving the crime of money laundering and law enforcement against the crime of money laundering is still ongoing. there are obstacles both in terms of substantive law (material law) and in terms of procedural law (formal law) as regulated in Law Number 8 of 2010.